Learning Using the Jigsaw Type I Cooperative Model To Improve Students' Ability in Determining the Functional Compositions in Class X SMA Negeri 1 Barusjahe 2018/2019 Academic Year - Sembiring, Yonando (Al'Adzkiya Journal, 2022)
This research is descriptive research. This study aimed to determine whether learning by using the Jigsaw Type I Cooperative Model can improve students' ability to determine the function compositions in class X SMA Negeri 1 Barusjahe in the 2018/2019 academic year. The subjects in this study were students in class X SMA Negeri 1 Barusjahe in the 2018/2019 academic year with a total of 35 people. The object of this research was the students' mathematics learning mastery during the implementation of the Jigsaw Type I Cooperative Model to Improve Students' Ability to Determine Functional Compositions in Class X SMA Negeri 1 Barusjahe 2018/2019 Academic Year